2017
DOI: 10.1039/c6tb02808j
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional surface for blood contact with fibrinolytic activity, ability to promote endothelial cell adhesion and inhibit smooth muscle cell adhesion

Abstract: Blood compatible materials are required for a wide variety of medical devices. Despite many years of intensive effort, however, the blood compatibility problem, in particular the ability to prevent thrombosis, remains unsolved. Based on the knowledge that the vascular endothelium, the ultimate blood contacting surface, draws on several mechanisms to maintain blood fluidity, it seems reasonable that analogous multifunctionality should be the goal for blood compatible biomaterials.In the present work, a polyuret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…However, due to the incomplete coverage of endothelial cells (ECs) on the surface of vascular substitutes (causing intimal hyperplasia), tissue-engineered grafts for small vessels often cause occlusions (thrombosis) [ 4 ]. Complete endothelialization along the inner wall of a scaffold holds promises in solving this issue [ 5 , 6 ]. Using such a method, the in vitro expanded patient-derived ECs are firstly seeded on the luminal surface of the scaffold, and allowed to form a monolayer of evenly distributed ECs prior to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the incomplete coverage of endothelial cells (ECs) on the surface of vascular substitutes (causing intimal hyperplasia), tissue-engineered grafts for small vessels often cause occlusions (thrombosis) [ 4 ]. Complete endothelialization along the inner wall of a scaffold holds promises in solving this issue [ 5 , 6 ]. Using such a method, the in vitro expanded patient-derived ECs are firstly seeded on the luminal surface of the scaffold, and allowed to form a monolayer of evenly distributed ECs prior to transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Surface endothelialization is a promising approach for the improvement of blood compatibility, and heparin and heparin mimetics have been widely used as modifiers to promote this effect. ,,, It was thus of interest to investigate the behavior of ECs on our PU surfaces grafted with PSS, PMAG, and P­(SS- co -MAG).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that different surfaces (stainless steel, PU, poly­(ethylene glycol) diacrylate hydrogel scaffolds, silk fibroin scaffolds, etc.) modified with heparin or heparin mimics showed an inhibitory effect on HUVSMC adhesion and proliferation. , …”
Section: Resultsmentioning
confidence: 99%
“…As the content of LysMA increases, the adhesive strength of the hydrogel rst increases to a maximum value of 40.1 kPa and then decreases. This may be attributed to the inner electrostatic interactions of LysMA; 36 high LysMA content likely reinforces the hydrogen bonds between LysMA and decreases the interactions between the molecules and the substrate, resulting in a decrease in the adhesion value. 37 Therefore, optimal LysMA content is essential to enhance the adhesion of the Am-ZIL-LysMA hydrogel.…”
Section: Adhesion Propertiesmentioning
confidence: 99%